Variables Affecting the Creativity of Undergraduate Students at Nakhon Ratchasima Rajabhat University - Banjob Boonchan; Phadungchai Pupat; Boonchan Seesan (My University, 2015)
This descriptive research aims to investigate the construct validity of selected variables affecting the creativity of undergraduate students at Nakhon Ratchasima Rajabhat University. Seven hundred and sixty students participated in this study. They were tested on items relating to their creativity. The results showed that executive administration, teaching, instructional attitudes, motivation, and personality variables affected the creativity of the undergraduates. Creativity consisted of originality, fluency, flexibility, and elaboration. All factor loadings were over 0.30. After confirmatory factor analysis on creativity, the results showed an acceptable goodness-of-fit (x2 = 0.51, df = 1, p-value = 0.47497, RMSEA = 0.000). This shows that creativity measured by the creativity test is in accordance with the empirical data. Executive administration consists of policy, mission, and identity. Teaching consists of objectives, content, activity, and evaluation components. Instructional climate consisted of support, acceptance and participation. Motivation consists of needs, drives, and satisfaction. Personality consists of freedom, trust, and self-esteem. The results of the CFA indicated that each construct was well represented by the items used for the measurements.
Keywords: Creativity in Education and Neuroscience